The More You Know: Information Effects on Job Application Rates in a Large Field Experiment - Gee, Laura K. (Management Science, 2018)
This paper presents the results from a 2.3-million-person field experiment that varies whether or not a job seeker sees the number of applicants for a job posting on a large job-posting website, LinkedIn. This intervention increases the likelihood that a person will finish an application by 3.5%. Women have a larger increase in their likelihood of finishing an application than men. Overall, adding this information to a job posting may offer a light-touch way to both increase application rates and alter the diversity of the applicant pool. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2994. This paper was accepted by John List, behavioral economics.